Coexistence of memory and threshold switching behaviors in natural milk-based organic memristor. (4th June 2021) - Zhang, Peng; Zhang, Jiahui; Wang, Kunjie; Wang, Li; Liu, Xianrong; Jing, Yan; Xu, Benhua
Abstract: Natural biomaterials have attracted great interest for the fabrication of biocompatible memristors. Here, dense and smooth milk films were deposited on the Pt/SiO2 /Si substrate by spin-coating method and resistive switching (RS) devices based milk films with the configuration of Ag/milk/Pt/SiO2 /Si are fabricated for the first time. Furthermore, memory RS (MRS) and threshold RS (TRS) effects coexist in the devices, which can be controlled by appropriately setting the compliance current ( I cc ). The current conduction mechanisms of the devices with MRS and TRS effects are controlled by typical trap-controlled space charge limited current (SCLC) conduction and filamentary conduction mechanism. The good RS performances of the milk-based devices make them promising for sustainable bioelectronics and novel logic device applications.